Distribution of trace elements during coal Gasification：The effect of upgrading method. (20th July 2018) - Chen, Guanyi; Sun, Yunan; Yan, Beibei; Yang, Ruilei; Liu, Bin; Cheng, Zhanjun; Ma, Wenchao
Abstract: A combination of upgrading and gasification process seems quite promising to cleanly utilize low-rank coal (LRC). The distribution of trace elements in this process has rarely been researched. In this study, four upgrading methods for LRC (evaporative drying, pyrolysis upgrading, microwave drying and hydrothermal dewatering (HTD)) were used and then the upgraded coal (UC) was gasified with investigation on the distribution and emissions of 13 trace elements (beryllium, vanadium, chromium, manganese, cobalt, nickel, copper, zinc, arsenic, selenium, cadmium, mercury and lead). The relative enrichment factors (RE) were introduced to quantitatively compare four different upgrading methods. The results show that gasification of UC helps controlling trace element of LRC by reducing its contents in feedstock and enhancing the ash enrichment. Different upgrading methods have their specific effects on different trace elements, respectively. Microwave drying presents to be best for most trace elements enriched to ash, in particular for beryllium, vanadium, chromium, manganese, cobalt, copper. Majority of 13 elements could reduce roughly 50% of the content through microwave drying method, and the reduction of lead reaches 72.5%. It seems the upgrading is quite effective in controlling emissions of trace elements from coal gasification. Highlights: Upgrading of low-rank coal could enhance its quality for gasification and reduce the contents of some trace elements in the coal. Microwave drying was the best in reducing contents of trace elements in coal, followed by pyrolysis upgrading. Upgrading technology could promote the enrichment of trace elements in ash. Among 4 upgrading methods, upgraded coal obtained from evaporative drying and microwave drying could remain more trace elements in ash.